Social traits modulate attention to affiliative cues - Moore, Sarah R.; Fu, Yu; Depue, Richard A. (Frontiers in Psychology, 2014)
Neurobehavioral models of personality suggest that the salience assigned to particular classes of stimuli vary as a function of traits that reflect both the activity of neurobiological encoding and relevant social experience. In turn, this joint influence modulates the extent that salience influences attentional processes, and hence learning about and responding to those stimuli. Applying this model to the domain of social valuation, we assessed the differential effects on attentional guidance by affiliative cues of (i) a higher-order temperament trait (Social Closeness), and (ii) attachment style in a sample of 57 women. Attention to affiliative pictures paired with either incentive or neutral pictures was assessed using camera eye-tracking. Trait social closeness and attachment avoidance interacted to modulate fixation frequency on affiliative but not on incentive pictures, suggesting that both traits influence the salience assigned to affiliative cues specifically.